SISTEM INFORMASI PERNIKAHAN PADA KANTOR URUSAN AGAMA MARO SEBO ILIR: Administration, Information System, Marriage Administration, Office Of Religious Affairs, Waterfall Model - Riswan, Riswan; Nilawati, Nilawati; Della, Della (LP2M Universitas Nurdin Hamzah, 2025)
This study aims to design and develop a Marriage Information System that can assist the KUA in managing marriage data more effectively, efficiently, and accurately. The research employs the Waterfall Model approach, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. Data were collected through observation, interviews with KUA staff, and documentation studies of marriage records. The results indicate that the developed information system is capable of managing prospective bride and groom data as well as marriage records in a structured manner, accelerating the recording and retrieval process, and producing more accurate administrative reports. Moreover, the system reduces recording errors that commonly occur in manual processes. Therefore, the implementation of this information system contributes to improving the effectiveness and transparency of marriage administration services at KUA Maro Sebo Ilir and supports the digitalization of public services within the Ministry of Religious Affairs.